1972
DOI: 10.1111/j.1151-2916.1972.tb11235.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline‐Earth‐Fluoride—LaF3 Systems with Implications for Electroslag Melting

Abstract: Liquidus and solidus curves in the systems CaF2-LaF,, SrF,-LaF,, BaF,-LaF,, and MgF2-LaFJ under % atm helium pressure were determined by thermal analysis as an aid in the selection of suitable fluxes for electroslag melting of reactive metals. The systems CaF,-LaF,, SrF,-LaF,, and BaF,-LaFd each contain (1) one eutectic, (2) no intermediate phases, and (3) two solid solutions whose lattice parameters vary linearly with composition. The liquidus curves in the systems SrF,-LaF, and BaF,-LaF3 exhibit maxima. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…17,18 Moreover, the solubility limit of BaF 2 in LaF 3 needs to be ascertained. 19,20 Roos et al have largely investigated the fluorine mobility on La 1−x Ba x F 3−x single-crystals: electrical, 21 electronic 22 and ionic 23 conductivities, bulk and interfacial polarization, 24 dielectric relaxation 25 and small-signal ac response. 26 They proposed the first equivalent circuits to model the impedance spectra 24 and they demonstrated that the electronic conductivity can be neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Moreover, the solubility limit of BaF 2 in LaF 3 needs to be ascertained. 19,20 Roos et al have largely investigated the fluorine mobility on La 1−x Ba x F 3−x single-crystals: electrical, 21 electronic 22 and ionic 23 conductivities, bulk and interfacial polarization, 24 dielectric relaxation 25 and small-signal ac response. 26 They proposed the first equivalent circuits to model the impedance spectra 24 and they demonstrated that the electronic conductivity can be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Recently, Fichtner et al observed a conduction maximum at x = 0.1 for mechanosynthesized powders 6 and thin films 34 and that the absence of sintering is detrimental to the conductivity. 35 The last aspect of La 1−x Ba x F 3−x characterization concerns 19 F NMR experiments, which are particularly useful to probe accurately the environment and mobilities of fluoride ions. In the tysonite structure (P3 ˉc1), three crystallographic fluorine sites have different occupancies (F1 (12g), F2 (4d) and F3 (2a)).…”
Section: Introductionmentioning
confidence: 99%
“…Phase equilibria in the SrF 2 ‐LaF 3 system have been studied repeatedly, 1‐6 see Figure 1. In this eutectic type system (eutectic coordinates are 70 mol% LaF 3 , 1450°C), wide areas of solid solutions are formed based on the components: Sr 1− x La x F 2+ x with the fluorite‐type structure (cubic system, Space Symmetry Group (SSG) Fm Fmtrue3¯m) and La 1− y Sr y F 3− y with the structure of LaF 3 ‐tysonite (trigonal system, SSG P 3¯ c 1).…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with eqs. (13) and (14), because the free F I concentration increases exponentially with temperature, and so contributes to a further decrease of AH A.…”
Section: Lonic Conductivitymentioning
confidence: 99%
“…(14) and (23). The parameter A/-/~I 2 is calculated from data obtained on sample 1, under the assumption that x c equals the difference between the nominal impurity concentration and the dipole concentration in this sample.…”
Section: Dipole Concentrationsmentioning
confidence: 99%